2018
DOI: 10.1111/dme.13622
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Type 2 diabetes after gestational diabetes directed at the family context: a narrative review from the Danish Diabetes Academy symposium

Abstract: In this review, we aim to summarize knowledge about gestational diabetes mellitus (GDM) after delivery; with special focus on the potential of preventing Type 2 diabetes in a family context. The review expands on the key messages from a symposium held in Copenhagen in May 2017 and highlights avenues for future research. A narrative review of the symposium presentations and related literature is given. GDM is associated with increased short- and long-term adverse outcomes including Type 2 diabetes for both moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Feeling unmotivated, lack of enjoyment of exercise or healthy food, low self‐worth, perception of ability and unwillingness to change were barriers relating to motivation identified in this review and have been similarly reported in previous literature 61,65 . Motivational interviewing techniques and patient‐centred approaches could be useful in improving motivation to engage in physical activity and healthy eating 67 .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Feeling unmotivated, lack of enjoyment of exercise or healthy food, low self‐worth, perception of ability and unwillingness to change were barriers relating to motivation identified in this review and have been similarly reported in previous literature 61,65 . Motivational interviewing techniques and patient‐centred approaches could be useful in improving motivation to engage in physical activity and healthy eating 67 .…”
Section: Discussionsupporting
confidence: 69%
“…Because of the strong influence of the family on women's lifestyle choices and the reliance on family for social support, lifestyle interventions for postpartum women should take a family‐focused approach 49,64 . Considering that the child's health and well‐being is a priority for postpartum mothers, proposing the need to be role models for their children may be an effective strategy to facilitate long‐term lifestyle change 17,65 . Changes at the community and policy level such as provision of childcare at exercise facilities and safe walking paths for mothers with pram may also be effective in promoting physical activity 66…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Nielsen and colleagues highlighted the importance of family-contextualised interventions to increase physical activity in women with a history of GDM (Nielsen et al, 2018). Their narrative review highlighted that “much remains to be understood about what such strategies should involve if they are to be effective” (p. 717), and emphasised the need for multiple avenues of intervention, from psychological to social approaches (Nielsen et al, 2018). This review aimed to fill that gap in understanding by exploring what factors women with previous GDM say is important to them when considering physical activity and how well these factors are represented in previous trials of physical activity interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The diabetes prevention programme participants had already developed impaired glucose tolerance, and women were enrolled an average of 12 years after their first GDM pregnancy. These women were much further along the trajectory to develop DAP and at a different life stage compared with women within 5 years of GDM pregnancy (Kragelund Nielsen, Groth Grunnet, & Terkildsen Maindal, ; Nielsen, Kapur, Damm, de Courten, & Bygbjerg, ). Importantly, at least half of women with a GDM history who develop DAP do so within 5 years of a GDM pregnancy (Kim, Newton, & Knopp, ; Pace, Brazeau, Meltzer, Rahme, & Dasgupta, ).…”
Section: Introductionmentioning
confidence: 99%